2014
DOI: 10.2174/1389557513666131211105554
|View full text |Cite
|
Sign up to set email alerts
|

Surface Binding of Toxins and Heavy Metals by Probiotics

Abstract: Removal of toxic metals and toxins using microbial biomass has been introduced as an inexpensive, new promising method on top of conventional methods for decontamination of food, raw material and concentrated. In this article the potential application of lactic acid bacteria and yeasts as the most familiar probiotics to eliminate, inactivate or reduce bioavailability of contamination in foods and feed has been reviewed. After fast glance to beneficial health effects and preservative properties of lactic acid b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
132
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 173 publications
(139 citation statements)
references
References 0 publications
2
132
0
5
Order By: Relevance
“…Similarly, the increased in cell proliferation in the treatment could be attributed to possible removal of patulin and repair of the cells from cell damage induced by patulin exposure. The protective effect of LGG resulting in cells rescue was expected as Zoghi et alin their study, reported that probiotic bacteria is capable of binding patulin and other mycotoxins in vitro by metabolic conversion of toxins through bacterial enzymatic action (El-Nezami et al, 2006;Zoghi et al, 2014). El-Nezami et al (2000) have demonstrated that lactic acid bacteria, most of which are probiotic, are also capable of detoxifying aflatoxins B, a well know potent carcinogen, which was a major contributor of liver cancer in central Africa and China (El-Nezami et al, 2000, IARC, 2002.…”
Section: Cell Proliferation and Effect Of Lactobacillus Rhamnosus Ggmentioning
confidence: 94%
“…Similarly, the increased in cell proliferation in the treatment could be attributed to possible removal of patulin and repair of the cells from cell damage induced by patulin exposure. The protective effect of LGG resulting in cells rescue was expected as Zoghi et alin their study, reported that probiotic bacteria is capable of binding patulin and other mycotoxins in vitro by metabolic conversion of toxins through bacterial enzymatic action (El-Nezami et al, 2006;Zoghi et al, 2014). El-Nezami et al (2000) have demonstrated that lactic acid bacteria, most of which are probiotic, are also capable of detoxifying aflatoxins B, a well know potent carcinogen, which was a major contributor of liver cancer in central Africa and China (El-Nezami et al, 2000, IARC, 2002.…”
Section: Cell Proliferation and Effect Of Lactobacillus Rhamnosus Ggmentioning
confidence: 94%
“…Unlike the food industry's efforts to produce safe food, it is likely that food can be either contaminated during the process or prepared from contaminated raw materials (1). Therefore, food products consumers can be environmentally exposed to both intentional and unintentional additives and pollutants which can have adverse effects on health over time.…”
Section: Contextmentioning
confidence: 99%
“…Therefore, food products consumers can be environmentally exposed to both intentional and unintentional additives and pollutants which can have adverse effects on health over time. Environmental contaminants such as heavy metals, pesticides and mycotoxins can be released to water and food production chain and lead to formation of unwanted harmful chemical compounds during processing, resulting in various adverse health effects and chronic toxicity, especially cancer (1)(2)(3). Cancer is a very serious and complicated disease created by out of control and irregular growth of cell (4), whose prevalence is remarkably increasing.…”
Section: Contextmentioning
confidence: 99%
See 2 more Smart Citations